Experimental study of a linear Fresnel reflection solar concentrating system - Zhang, Qian; Chen, Song; Yuan, Bin; Huang, Lei (Frontiers in Energy Research, 2023)
In this paper, a linear Fresnel reflection solar concentrator is proposed. The position, tilt angle and width of the glass mirrors placed in the same plane are different to ensure that all the reflected light falls on the flat focal plane or cylindrical focal surface. According to the focusing principle of the concentrator, two experimental system platforms ware built. When a flat focal plane is used to receive radiation from the sun, the intensity distribution of focal plane light spot is uniform in theory.The CCD measurement method is used to analyze the concentrated light spot under experimental conditions, and it is proved that the energy flux density on the focal plane is uniform. Placing monocrystalline silicon cells on the focal plane, the experimental results of p-v power generation voltammetry show that the power generation efficiency of monocrystalline silicon cell does not decrease due to the uniform solar energy density, which can reach 17.1%. The photothermal experiment is carried out by using one-dimensional tracking mode of sunlight. The concentrator reflects the sun's rays onto the vacuum collector tubes, heating the heat conduction oil flow in. The thermocouple measures the temperature of the heat conduction oil at the inlet and outlet of the vacuum collector tubes. The experimental photothermal conversion efficiency of this concentrator was analyzed and calculated through multiple groups of photothermal experiments, and compared with the theoretical concentrator efficiency. With two collector tubes in series, the theoretical photothermal conversion efficiency reaches 0.8 and the experimental photothermal conversion efficiency reaches about 0.74.